OMERTA: TANTANGAN PSIKOLOGI SOSIAL PENGUNGKAPAN KEJAHATAN KORUPSI - Rizma Afian Azhiim (Kajian Ilmu Kepolisian dan Anti Korupsi Universitas Bhayangkara Jakarta Raya, 2026)
The phenomenon of Omerta, or the code of silence, serves as a significant structural barrier in the investigation of corruption crimes in Indonesia. This culture protects corrupt networks through mechanisms that safeguard superiors, colleagues, and organized syndicates, thereby complicating the disclosure of grand corruption cases. This qualitative research aims to dissect the root causes of the Omerta phenomenon within the context of corruption in Indonesia and evaluate the investigative strategies employed by law enforcement, particularly the Corruption Eradication Commission (KPK). Utilizing a case study approach on the e-KTP corruption scandal, the results indicate that Omerta is rooted in strong patronage networks, blind loyalty, and systemic weaknesses in whistleblower protection. A permissive environment and partial legal implementation create a